2022
DOI: 10.3390/molecules27030854
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Content and Antioxidant and Antimicrobial Activities of Papaver rhoeas L. Organ Extracts Growing in Taounate Region, Morocco

Abstract: The objective of this study is to valorize Papaver rhoeas L. from the Taounate region of Morocco by determining the total polyphenol content (TPC), the total flavonoid content (TFC) and the antioxidant and antimicrobial activities of four organs. The quantification of TPC and TFC in root, stem, leaf and flower extracts (RE, SE, LE and FE, respectively) was estimated by the Folin–Ciocalteu reaction and the aluminum trichloride method, respectively. Two tests were used to assess antioxidant power: the DPPH test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…The calibration curve for quercetin and the regression equation, y = 11.786 + 0.0990, R 2 = 0.991, show that the flavonoid concentration equivalent to the quercetin concentrations of the hydroacetonic extract was equal to 0.067 ± 0.001 mg EQ/g, while the hydro-ethanolic resulted in 0.012 ± 0.001 mg EQ/g extract. The amount of total phenol and flavonoid content varies according on the plant part used [38]. In comparison with the result of another study carried out in Tunisia, where they were worked on the fruits of S. elaeagnifolium at different stages of ripening and with different solvents, the flavonoid contents of ethyl acetate extracts (61.09 ± 1.92 mg EQ/g extract), dichloromethane (34.17 ± 0.22 mg EQ/g extract), and methanol (17.62 ± 0.42 mg EQ/g extract) were determined for ripe fruits in this study.…”
Section: Total Polyphenols and Flavonoidsmentioning
confidence: 99%
“…The calibration curve for quercetin and the regression equation, y = 11.786 + 0.0990, R 2 = 0.991, show that the flavonoid concentration equivalent to the quercetin concentrations of the hydroacetonic extract was equal to 0.067 ± 0.001 mg EQ/g, while the hydro-ethanolic resulted in 0.012 ± 0.001 mg EQ/g extract. The amount of total phenol and flavonoid content varies according on the plant part used [38]. In comparison with the result of another study carried out in Tunisia, where they were worked on the fruits of S. elaeagnifolium at different stages of ripening and with different solvents, the flavonoid contents of ethyl acetate extracts (61.09 ± 1.92 mg EQ/g extract), dichloromethane (34.17 ± 0.22 mg EQ/g extract), and methanol (17.62 ± 0.42 mg EQ/g extract) were determined for ripe fruits in this study.…”
Section: Total Polyphenols and Flavonoidsmentioning
confidence: 99%
“…A lot of antibacterial infections can be effectively treated with aromatic and medicinal herbs [ 5 ], since they have no negative effects and contain a variety of secondary metabolites [ 6 ]. Moreover, herbal medicines continue to be the mainstay of therapy for major ailments in developing nations.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research has shown that antioxidants, which are used to combat free radicals, can also be utilized to treat some pathologies, including diabetes, cancer and neurodegenerative diseases. In contrast, many illnesses, including carcinogenicity, can be brought on by the usage of synthetic antioxidants [ 5 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, 2.5 mL of serial dilution of rutin (0.025, 0.037, 0.050, and 0.075 mg/mL) was added to the mixture and incubated again for 40 min at 37°C. Finally, the absorbance of the resulting mixture was read at a wavelength of 415 nm by spectrophotometer (Shimadzu Co., model number: UVmini 1240; Hmamou et al, 2022).…”
Section: Methodsmentioning
confidence: 99%